Different isolation approaches lead to diverse glycosylated extracellular vesicle populations. Issue 1 (1st December 2019) - Freitas, Daniela; Balmaña, Meritxell; Poças, Juliana; Campos, Diana; Osório, Hugo; Konstantinidi, Andriana; Vakhrushev, Sergey Y.; Magalhães, Ana; Reis, Celso A.
ABSTRACT: Extracellular vesicles (EVs) are a heterogeneous group of small secreted particles involved in intercellular communication and mediating a broad spectrum of biological functions. EVs cargo is composed of a large repertoire of molecules, including glycoconjugates. Herein, we report the first study on the impact of the isolation strategy on the EV populations' glycosylation profile. The use of different state-of-the-art protocols, namely differential ultracentrifugation (UC), total exosome isolation (TEI), OptiPrep TM density gradient (ODG) and size exclusion chromatography (SEC) resulted in EV populations displaying different sets of glycoconjugates. The EV populations obtained by UC, ODG and SEC methods displayed similar protein and glycan profiles, whereas TEI methodology isolated the most distinct EV population. In addition, ODG and SEC isolation protocols provided an enhanced EV glycoproteins detection. Remarkably, proteins displaying the tumour-associated glycan sialyl-Tn (STn) were identified as packaged cargo into EVs independently of the isolation methodology. STn carrying EV samples isolated by UC, ODG and SEC presented a considerable set of cancer-related proteins that were not detected in EVs isolated by TEI. Our work demonstrates the impact of using different isolation methodologies in the populations of EVs that are obtained, with consequences in the glycosylation profile of the isolated population. Furthermore, our results highlight the importance of selecting adequate EV isolation protocols and cell culture conditions to determine the structural and functional complexity of the EV glycoconjugates.